PENDIDIKAN ISLAM MULTIKULTURAL - Zulkarnain Dali (Universitas Islam Negeri Fatmawati Sukarno, 2017)
Multicultural education does not mean merely celebrating diversity. Especially if the existing society is still full of discrimination and racist. In such a case, multicultural education is more appropriately directed as an allocation to create a tolerant free society. Multiculturalism education is intended to respond to the phenomenon of ethnic, socio- cultural conflicts that often arise in the midst of multicultural society, multicultural faces in this country up to now like a fire in the chaff that one day can lead to the temperature of political, religion, social culture that heats up, which allowing the conflict to reappear. Multicultural education can be used at both the descriptive and normative levels, which illus- trates the issues and issues of education related to the multicultural community. He further includes an understanding of considerations of educational policies and strategies in multicultural societies that clearly cover subjects such as: tol- erance, themes of ethno-cultural differences and religion: the dangers of discrimination, conflict resolution, democracy and plurality , universal humanity and so forth